Optical waveguides fabricated in atomic layer deposited Al2O3 by ultrafast laser ablation - Lizarraga-Medina, Eder German; Castillo, Gabriel R.; Jurado, Jorge Adolfo; Caballero-Espitia, Diana Laura; Camacho-Lopez, Santiago; Contreras, Oscar; Santillan, Ricardo; Marquez, Heriberto; Tiznado, Hugo (Results in optics, 2021)
•Atomic layer deposited Al2O3 optical rib waveguides by ultrafast laser ablation.•Good confinement and low loss at the visible range.•Fabrication method is fast and reliable for prototyping of photonic components. We report on the fabrication of optical waveguides by ultrafast laser ablation of Al2O3. First, a thin film was grown by atomic layer deposition (ALD) on fused silica substrate, followed by laser ablation micromachining the surface material in order to produce a rib waveguide. A multimode behavior of the waveguide and propagation loss of 3.8 dB/cm was measured at 632.8 nm. Microstructural characterization showed that roughness is the major issue to overcome the propagation losses. Results obtained in this work suggest a viable methodology for the fabrication of optical waveguides for potential applications in integrated photonics.